Functional alteration of the beta-adrenergic receptor during desensitization of mammalian adenylate cyclase by beta-agonists. - Kassis, S (1984)
Exposure of several mammalian cell lines to isoproterenol resulted in a desensitization of the beta-adrenergic receptor-adenylate cyclase system in membranes isolated from the cells. Under the experimental conditions chosen, desensitization was accompanied by a minimal loss of beta-receptors. The cells tested included HeLa, S49 cyc- lymphoma, and rat glioma C6. The functional activity of the beta-receptors was determined by coupling them to a foreign adenylate cyclase by membrane fusion. The donor membranes were treated to inactivate the regulatory and catalytic components of adenylate cyclase. The acceptor membranes were from Friend erythroleukemic cells (Fr cells), which lack beta-receptors, and HeLa cells treated overnight with isoproterenol to eliminate their receptors. The fused membranes were assayed for agonist-stimulated activity, which was always reduced when the donor beta-receptors were from the desensitized membranes. The desensitization appeared to be specific for beta-receptors, as the activity of other receptors and cyclase components was not altered. By fusing HeLa membranes with intact Fr cells, we directly measure the intrinsic activity of native and desensitized beta-receptors. For an equal amount of transferred beta-receptors, the activity was 40%-50% lower when the donor membranes were from desensitized cells. Our results clearly indicate that desensitization mediated by a beta-agonist in mammalian cells results in a functional alteration of the beta-receptor.